Love Grounding Cooler as a Warning to Last-Day Believers - Djone Georges Nicolas; Marlianti Hasibuan; Messyana Galatia Nainggolan; Yosia Simatupang; Dasman Waspada Waruwu (Jurnal Multidisiplin Madani, 2022)
The purpose of this study is to analyze whether the growing coldness of love in the lives of some believers is a warning sign for them in these last days. The approach in this study is a descriptive qualitative method with data collection through various sources such as the Bible and literature, journals, books and interviews. Indonesian social media is currently buzzing with a dramatic case of the premeditated murder of a police officer. Ironically, both those who planned the murder, the victim and who executed or shot the victim are all Christians, which raises a fundamental question: where is love known as the hallmark of the Christian faith? Is the growing love in the lives of some believers a warning sign to them in these last days? The result: The growing coldness of love is a warning to the latter-day believers to repent because some of them continue to live in self-serving worldly passions and ignore the central principle found in Christianity: the love for God reflected through love for each other